THE IMPACT OF THE LEVELS OF EDUCATION ON THE PERCEPTION OF CORPORATE SOCIAL RESPONSIBILITY - Karabašević, Darjan; Petrović, Gordana; Maksimović, Mlađan (Poslovna ekonomija, 2017)
The concept of corporate social responsibility in the broadest sense means the ways in which companies communicate with their stakeholders. The aim is to establish a balance between the economic, social and environmental aspects of the environment. In recent years, corporate social responsibility in Serbia is becoming more and more interesting. Serbia is, as a country, still in the process of transition with economic and social problems that further have an impact on the lack of responsible behavior by companies. As companies have an impact on social development in the communities in which they operate, they therefore also have responsibility that extends beyond the boundaries of making a profit. An important feature of our society is the responsibility of ranking on a scale of values of successful and modern companies. The aim of the study was to examine the effect of educational level on the perception of the concept of corporate social responsibility. The research was carried out on the territory of Šumadija district. Respondents' answers were analyzed by applying the method analysis of variance (ANOVA).